Analisis Gerakan “Boikot Israel” Terhadap Kebijakan Impor Produk Pro Israel Ke Indonesia - Patria Kumara, Diva Zaidan (PERSPEKTIF, 2024)
The problem focuses on Indonesia's import policy in the midst of the heated conflict between Israel and Palestine which has led to protests about this policy. Using the theoretical basis of the New Social Movement by Sukmana in 2016. This research method is descriptive qualitative research. The subject of observation is the Indonesian people involved in the boycott Israel movement. Data is collected by understanding material in scientific articles, news sites and official government websites.  The type of data used is qualitative data. This study found that 65% of Indonesians support the boycott of Israeli products and believe that this movement can influence government policy. Further efforts are needed such as more intensive public awareness campaigns and lobbying the government to review its import policy from Israel.